2012
DOI: 10.1038/ajg.2012.25
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Healing Erosive Esophagitis With a Proton Pump Inhibitor: The More the Merrier?

Abstract: Patients with erosive esophagitis (EE) account for 30 % of patients with gastroesophageal refl ux disease; only a minority of these patients fail to achieve healing on treatment with a proton pump inhibitor (PPI), once-daily, for 8 weeks. For those patients with EE who have failed to heal on a PPI, given once-daily, current practice is to double the PPI dose although there is little published evidence to support this. In this issue of the American Journal of Gastroenterology , authors from Japan have demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…13,18 Consequently, patients with EE receiving standard dose PPIs may still suffer from heartburn or regurgitation despite a complete resolution of the esophageal inflammation. 19 Moreover, even when continuing the initial healing dose as maintenance treatment for a period of 6 months, 15-23% of the patients with LA-A or LA-B, respectively, and 24-41% with LA-C or LA-D, respectively, relapsed while on treatment. 20 Higuchi et al 8 showed that (after a mean 1.1 years of PPI therapy) approximately 40% of patients did not achieve remission of esophageal inflammation and that healing of esophageal inflammation was significantly lower (42%) in patients with severe EE compared with patients having LA-A (71%).…”
Section: Advanced Grades Of Erosive Esophagitismentioning
confidence: 99%
“…13,18 Consequently, patients with EE receiving standard dose PPIs may still suffer from heartburn or regurgitation despite a complete resolution of the esophageal inflammation. 19 Moreover, even when continuing the initial healing dose as maintenance treatment for a period of 6 months, 15-23% of the patients with LA-A or LA-B, respectively, and 24-41% with LA-C or LA-D, respectively, relapsed while on treatment. 20 Higuchi et al 8 showed that (after a mean 1.1 years of PPI therapy) approximately 40% of patients did not achieve remission of esophageal inflammation and that healing of esophageal inflammation was significantly lower (42%) in patients with severe EE compared with patients having LA-A (71%).…”
Section: Advanced Grades Of Erosive Esophagitismentioning
confidence: 99%
“…One trial [ 16 ] assessed the efficacy of standard dose of esomeprazole QD versus lansoprazole BID for GERD. In the United States and Europe, as well as many other countries around the world, rabeprazole 20 mg is considered as the standard dose for GERD therapy [ 20 ]. But in Japan, rabeprazole 10 mg is approved as a standard dose and 20 mg as a double dose [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…This effect could be due to bias but a systematic review has suggested that esomeprazole is more effective than standard doses of other PPIs used in the trial. It is possible that other PPIs used twice daily rather than once daily may have had a similar benefit to esomeprazole and this should be evaluated in future studies. This was a secondary outcome and therefore subjects with other reasons for sleep disturbance (e.g.…”
Section: Discussionmentioning
confidence: 99%